2010
DOI: 10.1038/nrrheum.2010.181
|View full text |Cite
|
Sign up to set email alerts
|

Chronic inflammation in FMF: markers, risk factors, outcomes and therapy

Abstract: Familial Mediterranean fever (FMF) is the most common of the hereditary periodic fever syndromes. Although the typical clinical course of FMF is characterized by bouts of painful inflammation, this presentation represents only the tip of the iceberg. In many patients inflammation can persist in attack-free periods, as shown by high levels of acute-phase proteins, cytokines and inflammation-induced proteins. This subclinical inflammation puts patients at risk of developing complications such as anemia, splenome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
138
3
17

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 198 publications
(162 citation statements)
references
References 68 publications
4
138
3
17
Order By: Relevance
“…This condition is known as Uhthoff's phenom-enon [32]. It is explained by a conduction block because of the ionic channels properties change under high temperature [33]. However, the effect of heat changes on MS can be multi-factorial.…”
Section: Discussionmentioning
confidence: 99%
“…This condition is known as Uhthoff's phenom-enon [32]. It is explained by a conduction block because of the ionic channels properties change under high temperature [33]. However, the effect of heat changes on MS can be multi-factorial.…”
Section: Discussionmentioning
confidence: 99%
“…AA amyloidosis is the most devastating complication of FMF (7). Despite colchicine prophylaxis, amyloidosis may still prevail in about 5% of FMF patients, leading eventually to end-stage kidney disease in almost all patients.…”
Section: Introductionmentioning
confidence: 99%
“…Clinically, FMF is characterized by self-limited attacks of severe inflammation with fever and sterile serositis, each lasting up to 4 days (3)(4)(5)(6). Chronic inflammation and its sequelae, including anemia, splenomegaly, continuously elevated acute-phase reactants, and amyloidosis may also occur in 30-60% of untreated or treatment-refractory patients (7). The MEditerranean FeVer gene (MEFV) was cloned in 1997, but only recently was it found that the protein encoded by it (pyrin/marenostrin) is a sensor protein of bacterial antigens that is used to promote inflammation (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…In FMF patients, the effusion of neutrophils in serous cavities causes infl ammatory attacks, which results in increase in acute phase reactants [1]. Various studies have reported that the levels of interleukin-6 (IL-6), interleukin-10 (IL-10), and tumor necrosis factor-alpha (TNF-) increase during and between FMF attacks [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Familial Mediterranean Fever (FMF) is an autosomal recessive disease characterized by recurrent fever, abdominal pain, monoarthricular and/or oligoarthricular arthritis, polyserositis, and erysipelas-like erythema [1] .FMF has been predominantly found in ethnic groups living around the Mediterranean basin (Jews, Arabs, Turks, and Armenians) [1].…”
Section: Introductionmentioning
confidence: 99%